2005
DOI: 10.3390/s5120509
|View full text |Cite
|
Sign up to set email alerts
|

Softlithography in Chemical Sensing – Analytes from Molecules to Cells

Abstract: Imprinting is a flexible and straightforward technique to generate selective sensor materials e.g. for mass-sensitive detection. Inherently, the strategy suits both molecular analytes and entire micro organisms or cells. Imprinted polyurethanes e.g. are capable of distinguishing the different xylene isomers with very appreciable selectivity factors. Combining imprinted titanates with surface transverse wave resonators (STW) leads to a powerful tool for detecting engine oil degradation, which is an excellent ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…Due to space limitations we do not present a comprehensive list of molecular templates, but rather explain the basic principles of noncovalent molecular imprinting, and address the most important new polymer chemistry and micro-/nanofabrication techniques that are being introduced into the molecular imprinting area. For more extensive discussions on topics uncovered in this chapter, we refer to several excellent reviews already existing in the literature, for example, on general radical polymerization [7], specialized and noncommercial functional monomers [8,9], and molecular imprinting using condensation crosslinking reactions [10]. Noncovalent molecular imprinting is the most commonly used approach in research laboratories today.…”
Section: Introductionmentioning
confidence: 99%
“…Due to space limitations we do not present a comprehensive list of molecular templates, but rather explain the basic principles of noncovalent molecular imprinting, and address the most important new polymer chemistry and micro-/nanofabrication techniques that are being introduced into the molecular imprinting area. For more extensive discussions on topics uncovered in this chapter, we refer to several excellent reviews already existing in the literature, for example, on general radical polymerization [7], specialized and noncommercial functional monomers [8,9], and molecular imprinting using condensation crosslinking reactions [10]. Noncovalent molecular imprinting is the most commonly used approach in research laboratories today.…”
Section: Introductionmentioning
confidence: 99%
“…6 The first successful attempt of blood typing using MIPs was reported by Dickert and his group in 2005. 7,8 It was shown that it is possible to recognise different types of blood cells through the surface imprinting of whole erythrocytes on the sensor surface of microbalances covered with a 100-nm polyurethane layer. Nevertheless, the necessity to use whole blood cells in combination with microbalances was a rather complicated approach from manufacturing point of view and was not compatible with individual analytical tests, which should be portable, affordable and easy to use.…”
mentioning
confidence: 99%
“…The single-channel piezoelectric immunosensor arrangement was found sufficiently stable under laboratory conditions, though differential arrangements with a reference sensing are might provide even better stability and reproducibility of signals [17]. …”
Section: Resultsmentioning
confidence: 99%